2022
DOI: 10.3389/fgene.2022.909251
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 and p63 in the Regulation of Cancer Stemness

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a transcription factor with many important functions in normal and transformed cells. STAT3 regulatory activities are highly complex as they are involved in various signaling pathways in different cell types under different conditions. Biologically, STAT3 is a regulative factor for normal and cancer stem cells (CSCs). Tumor protein p63 (p63), a member of the p53 protein family, is involved in these biological processes and is also physically and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In favour of an indirect mechanism, we posit that HIF1α perturbation, which inhibits mesenchymal gene expression, destabilises p63 and hence the E/M state. Moreover, GPx2 KD may regulate this process via oxidation/inactivation of tyrosine phosphatases by ROS [ 47 ], which results in EGFR/STAT3 signalling, leading to p63 gene transcription [ 48 , 49 ]. Otherwise, HIF1α may activate Wnt signalling in hypoxic niches, thereby upregulating p63, a well-documented Wnt target gene [ 47 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In favour of an indirect mechanism, we posit that HIF1α perturbation, which inhibits mesenchymal gene expression, destabilises p63 and hence the E/M state. Moreover, GPx2 KD may regulate this process via oxidation/inactivation of tyrosine phosphatases by ROS [ 47 ], which results in EGFR/STAT3 signalling, leading to p63 gene transcription [ 48 , 49 ]. Otherwise, HIF1α may activate Wnt signalling in hypoxic niches, thereby upregulating p63, a well-documented Wnt target gene [ 47 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that aberrant activation of STAT3 signaling promotes tumor growth, 46 invasion, metastasis, 48 and resistance to therapy. 49 The JAK/STAT and Wnt-β-catenin pathways have been identified as pivotal players in tumorigenesis. Notably, research has demonstrated a direct interaction between STAT3 and β-catenin in the nucleus, 50 with STAT3 positively regulating β-catenin’s transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EZH2-activated RUNX3 acts as an inhibitor of both SETD1 and ΔNp63α [ 194 ]. ΔNp63 is often overexpressed in SCCs, in which it acts as a master regulator of CSCs maintenance via its functional connection with signal transducer and activator of transcription 3 (STAT3), assigning STAT3 induces ΔNp63 expression through binding to its promoter [ 195 197 ]. The gene encoding the chromatin-modifying protein that ACTL6A (Actin-like protein 6 A) is coamplified with p63 locus in HNSCC and induces a CSC phenotype characterized by undifferentiated regenerative proliferation.…”
Section: P63 and Cancer Stem Cell In Epithelial Tumormentioning
confidence: 99%